Alkaline-heat-induced protein co-assembly combined with hyaluronic acid surface modification for improving functional properties of pea protein - Yunan Chen; Chenkai Ma; Chunxia Zhou; Sichen Yang; Han Zhang; Zhibo Li; Qingguan Liu (Food Research International, 2026)

The effects of different grassland management methods on soil organic carbon components, enzyme activities and microbial communities in alpine meadows - Sun Chenchen; Liu Jiaxing; Hu Hangwei; Zuo Chao; Pan Sichen; Zhao Liang; Wang Shiping; Zhao Zongjian; Andreas Wilkes; Luo Caiyun (Agriculture, Ecosystems & Environment, 2026)

Rock Strength Estimation Using Drilling Vibration Signal - Mengjia Zhang; Zhongwen Yue; Wei Liu; Sichen Long; Wendal Victor Yue; Zengqiang Lv (Rock Mechanics and Rock Engineering, 2026)

Regulatory mechanisms of adipocyte differentiation and fat deposition in pigs: Implications for meat quality improvement - Wenjing Wu; Xiao Cheng; Lu Shen; Shenpeng Zheng; Jie Zhang; Keke Liu; Sichen Yang; Xinrong Lian; Jin Zhang (Food Bioscience, 2026)

Corrigendum to “Enhanced electric field intensity in transverse microchannel charcoal electrode for facilitating electrochemical demulsification rate of oil-in-water droplets” [J Hazard Mater 511 (2026) 142186] - Hanqi Yang; Yiyi An; Sichen Liu; Yuwei Gu; Hongtao Yu (Journal of Hazardous Materials, 2026)

Driving mechanisms of adaptive strategies and heavy metal remediation potential in Artemisia lavandulaefolia during succession of abandoned Pb–Zn mining areas - Sichen Wang; Tianyi Pu; Xinqi Yuan; Chenyang Zhang; Shuaijie Sun; Dapeng Zong; Chang'e Liu; Changqun Duan; Liqiang Chen; Denggao Fu (Journal of Environmental Management, 2026)

Enhanced electric field intensity in transverse microchannel charcoal electrode for facilitating electrochemical demulsification rate of oil-in-water droplets - Hanqi Yang; Yiyi An; Sichen Liu; Yuwei Gu; Hongtao Yu (Journal of Hazardous Materials, 2026)

Enhanced Co Se covalency through controlled crystal phase transition for improved oxygen electrocatalysis - Sichen Huo; Xiaofeng Liu; Xiaoqin Xu; Mingyi Wang; Xinyu Wang; Yanjie Chen; Zhuang Cai; Hailong Li; Ziyu Zhao; Li Li; Hang Yue; Jinlong Zou (Chemical Engineering Journal, 2026)

Sustainable power system transition pathways: Regional decarbonization and resource conservation aided by small modular reactors - Dengcheng Han; David Z. Zhu; Guohe Huang; Sichen Gao; Lirong Liu (Resources, Conservation and Recycling, 2026)

Spatial and temporal pattern of the plankton community during the Water-Sediment Regulation in the Yellow River estuary - Lulei Liu; Sichen Zheng; Xiaomin Zhang; Fan Li; Biao Wu; Liqing Zhou; Zhihong Liu; Yuze Mao; Xiujun Sun (Ocean & Coastal Management, 2026)

Study of deformation and fragmentation of emulsion under electric field and shear based on fluid dynamics - Chuanke Liang; Zexin Liu; Sichen Wei; Nanjun Ma; Qijie Sun; Tao Li (Fuel, 2026)

Unlocking the hidden power: magnetic sludge biochar as a strengthening agent for anammox nitrogen removal advancement and microbial metabolic cooperation - Yuheng Zhu; Sichen Liu; Cheng Wang; Pingfeng Yu; Chongjun Chen (Chemical Engineering Journal, 2026)

PcUGT203E1 and PcUGT203B2 are involved in abamectin susceptibility in Panonychus citri - Yuchao Shen; Zehao Huang; Sichen Li; Wanfu Yao; Liu Liu; Shijun Fu; Shijiang Yu; Binbin Shao; Lili Ding; Qiqi Yang; Yang Li; Shaohui Zhang; et al. (Pesticide Biochemistry and Physiology, 2025)

Uncovering the potential of rosmarinic acid as a natural antimicrobial agent: effective inhibition of growth and biofilm formation in Bacillus cereus - Lu Tian; Qi Qi; Sichen Liao; Guoli Gong; Zhenbin Liu; Jiayi Zhang; Hongbo Li; Qing Sun; Haizhen Mo; Liangbin Hu (Food Control, 2025)

Characteristics of soil organic carbon components under different land-uses and their influencing factors in an alpine meadow on the Qinghai–Tibet Plateau - Caiyun Luo; Chao Zuo; Chenchen Sun; Sichen Pan; Jiaxing Liu; Liang Zhao; Shiping Wang; Zongjian Zhao; Andreas Wilkes (Journal of Soils and Sediments, 2025)

An evaluation of the sufficiency of natural soil seed banks to support vegetation restoration following severe soil degradation and heavy metal contamination - Ting Li; Yao Liu; Chaoyanjie Zhang; Sichen Wang; Changqun Duan (Plant and Soil, 2025)

Evaluating biochar for adsorption of ammonium nitrogen in wastewater:insights into modifications and mechanisms - Yuheng Zhu; Sichen Liu; Hanbo Chen; Pingfeng Yu; Chongjun Chen (Environmental Research, 2025)

Biotic and abiotic drivers of soil carbon, nitrogen and phosphorus and metal dynamic changes during spontaneous restoration of Pb–Zn mining wastelands - Sichen Wang; Ting Li; Xinqi Yuan; Ji Yu; Zhifei Luan; Zhaolai Guo; Yadong Yu; Chang’e Liu; Changqun Duan (Journal of Hazardous Materials, 2025)

Size effects on the variation in the pressure of CO2 fracturing device based on material point method - Yun Feng; Houlu Sun; Wei Liu; Guangjin Wang; Sichen Long; Zhongwen Yue (Gas Science and Engineering, 2025)

Hox-determined appendage regeneration restores cockroach courtship rituals - Xingmei Mai; Mingtao Liao; Fangming Zhao; Ethan Yihao Li; Fangzheng Liu; Renaguli Aisa; Sichen Wu; Nan Chen; Sheng Li; Chonghua Ren (Science China Life Sciences, 2025)

Temporal variations of N and P losses via surface runoff from Chinese farmland after fertilisation - Luoqi Zhao; Denggao Fu; Ting Li; Xinqi Yuan; Sichen Wang; Change Liu; Changqun Duan (Soil and Tillage Research, 2025)

Enhancing anammox activity and mitigating Cu²⁺ inhibition through different biochar additions: Short-term impacts on nitrogen removal efficiency, sludge characteristics, and microbial community - Sichen Liu; Qianfei Cao; Yuheng Zhu; Peng Wu; Wei Jin; Chongjun Chen (Journal of Environmental Chemical Engineering, 2025)

Engineering a carbon dot-decorated fluorescent nanoplatform to promote heavy metal reutilization and photothermal evaporation with antibacterial activity - Fei Yan; Sichen Liu; Xiaokui Huo; Guobiao Liang; Fangyu Yang; Baojing Zhang; Lei Feng; Tony D. James; Meng Li (Chemical Engineering Journal, 2025)

Improvement of soil nutrient cycling by dominant plants in natural restoration of heavy metal polluted areas - Ting Li; Sichen Wang; Luoqi Zhao; Xinqi Yuan; Yuhan Gao; Denggao Fu; Chang'e Liu; Changqun Duan (Environmental Research, 2024)

Phenol inhibition and recovery strategies of anaerobic ammonium oxidation (anammox) in wastewater: Mechanisms and practical implications - Wenqi Li; Sichen Liu; Faqian Sun; Cheng Wang; Yayi Wang; Chongjun Chen (Chemical Engineering Journal, 2024)

Turbulence and sediment deposition in a channel with floating vegetation - Ziqin Gui; Yuqi Shan; Chuan Li; Sichen Sun; Chao Liu (Journal of Hydrology, 2024)

Antimicrobial mechanism of morusin against Bacillus cereus and its potential as an antimicrobial agent - Sichen Liao; Guoli Gong; Jiapeng Fu; Jie Wang; Qi Qi; Lemei Hu; Chang Gao; Minmin Wang; Haoyue Cui; Jiaqiang Liu; Lu Tian (Food Bioscience, 2024)

Realizing high average zT in GeTe through band modulation and suppressing Ge vacancies - Haiqi Li; Chen Chen; Xinyu Wang; Dongyi Shen; Sichen Duan; Wenxuan Wang; Kejia Liu; Qian Zhang; Yue Chen (Chemical Engineering Journal, 2024)

Upgrading of dichloromethane to olefins by hydrodechlorination: Improving process efficiency by the addition of Fe to carbon nanotubes-supported Pd catalyst - Sichen Liu; Ana Iglesias-Juez; Ana B. Hungría; Maria Martin-Martinez; Jorge Bedia; Juan José Rodriguez; Luisa María Gómez-Sainero (Chemical Engineering Journal, 2024)

The role of information industry convergence in energy transition - Ruofan He; Congwen Su; Sichen Liu (Journal of Environmental Management, 2024)

Changes in soil microbe-mediated carbon, nitrogen and phosphorus cycling during spontaneous succession in abandoned Pb Zn mining areas - Sichen Wang; Xinqi Yuan; Ting Li; Jie Yang; Luoqi Zhao; Duanyang Yuan; Zhaolai Guo; Chang'e Liu; Changqun Duan (Science of The Total Environment, 2024)

Intra-tidal upwelling variability off Zhoushan Islands, East China Sea - Sichen Zhang; Lulu Qiao; Fei Gao; Zhigang Yao; Xingmin Liu (Estuarine, Coastal and Shelf Science, 2024)

Advanced nitrogen removal of landfill leachate treatment with anammox process: A critical review - Sichen Liu; Chuanyu Cai; Faqian Sun; Mengjie Ma; Tianyi An; Chongjun Chen (Journal of Water Process Engineering, 2024)

Soil microbial communities' contributions to soil ecosystem multifunctionality in the natural restoration of abandoned metal mines - Ting Li; Sichen Wang; Chang'e Liu; Yadong Yu; Mingming Zong; Changqun Duan (Journal of Environmental Management, 2024)

Opposite response of constructed wetland performance in nitrogen and phosphorus removal to short and long terms of operation - Luoqi Zhao; Denggao Fu; Xiaoni Wu; Change Liu; Xinqi Yuan; Sichen Wang; Changqun Duan (Journal of Environmental Management, 2024)

Impact of sediment size, channel velocity and plant density on sediment deposition inside Phragmites australis canopies - Sichen Sun; Yuqi Shan; Chunhao Yan; Chao Liu (Journal of Hydrology, 2023)

Research progress on pharmacological effects and mechanisms of cepharanthine and its derivatives - Liangliang Shi; Shuaizhe Wang; Shangzu Zhang; Jiawei Wang; Yaping Chen; Yangyang Li; Zhiwei Liu; Sichen Zhao; Benjun Wei; Liying Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Two-dimensional explainability method for fault diagnosis of fluid machine - Jiaquan Liu; Lei Hou; Sichen He; Xinru Zhang; Qiaoyan Yu; Kai Yang; Yu Li (Process Safety and Environmental Protection, 2023)

Optimization and control strategy of BOG re-liquefaction process for LNG vessels - Ting Guo; Lesheng Liu; Jiubing Shen; Qingfeng Jiang; Sichen Wu; Yanyan Zhou; Yi Liu (International Journal of Refrigeration, 2023)

Modulating electronic structure of interfacial Fe sites in Fe2N/CoFe2O4 nano-heterostructure for enhancing corrosion-resistance and oxygen electrocatalysis in zinc-air battery - Xiaoqin Xu; Mingyang Liu; Yao Nie; Cheng Wang; Wei Wang; Chuntao Liu; Xinyu Wang; Zhuang Cai; Xiaofeng Liu; Sichen Huo; Bin Liu; Jinlong Zou (Chemical Engineering Journal, 2023)

Nitric oxide-loaded nano- and microparticle platforms serving as potential new antifungal therapeutics - Sichen Liu; Daniel Zamith-Miranda; Rodrigo Almeida-Paes; Leandro Buffoni Roque da Silva; Parimala Nacharaju; Joshua D. Nosanchuk (Fungal Biology, 2023)

Soil microbial necromass: The state-of-the-art, knowledge gaps, and future perspectives - Hanqing Wu; Sichen Wan; Chujin Ruan; Wei Wan; Miao Han; Guowei Chen; Ying Liu; Kun Zhu; Chao Liang; Gang Wang (European Journal of Soil Biology, 2023)

Effects of Mud Supply and Hydrodynamic Conditions on the Sedimentary Distribution of Estuaries: Insights from Sediment Dynamic Numerical Simulation - Qian Zhang; Mingming Tang; Shuangfang Lu; Xueping Liu; Sichen Xiong (Journal of Marine Science and Engineering, 2023)
Estuaries are important sediment facies in the fluvial-to-marine transition zone, are strongly controlled by dynamic interactions of tides, waves, and fluvial flows, and show various changes in depositional processes and sediment distribution. Deep investigations on the sediment dynamic processes of the sand component of estuaries have been conducted; however, the understanding of how mud supply affects estuaries’ sedimentary characteristics and morphology is still in vague. Herein, the effects of mud concentration, mud transport properties, fluvial discharge, and tidal amplitude on the sedimentary characteristics of an estuary were systematically analyzed using sedimentary dynamic numerical simulation. The results show that the mud concentration has significant effects on the morphology of tidal channels in estuaries, which become more braided with a lower mud concentration, and straighter, with reduced channel migration, with a higher mud concentration. The mud transport properties, namely, setting velocity, critical bed shear stress for sedimentation, and erosion, mostly affect the ratio between the length and width (RLW) of the sand bar; a sheet-like sand bar with a lower RLW value develops in the lower settling velocity, while there are obvious strip shaped bars with a high RLW value in the higher settling velocity case. Moreover, the effects of hydrodynamic conditions on sedimentary distribution were analyzed by changing the tidal amplitudes and fluvial discharges. The results show that a higher tidal amplitude is often accompanied by a stronger tidal energy, which induces a more obvious seaward progradation, while a higher fluvial discharge usually yields a higher deposition rate and yields a greater deposition thickness. From the above numerical simulations, the statistical characteristics of tidal bars and mud interlayers were further obtained, which show good agreement with modern sedimentary characteristics. This study suggests that sedimentary dynamic numerical simulation can provide insights into an efficient quantitative method for analyzing the effects of mud components on the sediment processes of estuaries.

High-strength, self-initiated, wide pH range of underwater adhesive suitable for different severe environments - Junyu Ren; Guanben Du; Sichen Liu; Hongxing Yang; Xin Ran; Chang Liu; Tongda Liu; Zhi Li; Xiaojian Zhou; Wei Gao; Bei Zhou; Long Yang (Chemical Engineering Journal, 2023)

Altered topological properties of the intrinsic functional brain network in patients with right-sided unilateral hearing loss caused by acoustic neuroma - Zhiyuan Fan; Zhen Fan; Tianming Qiu; Liuxun Hu; Yuan Shi; Yunman Xia; Xiaoyi Sun; Yingjun Liu; Sichen Li; Mingrui Xia; Wei Zhu (Brain Imaging and Behavior, 2022)

Correction to: Organic Matter Pollution During the Spring Thaw in Hulun Lake Basin: Contribution of Multiform Human Activities - Wenlin Wang; Wenjing Li; Yan Yan; Bo Liu; Tanjing Wang; Sichen Mao; Ninghui Song; Huashan Dou; Wen Ao; Changxin Zou (Bulletin of Environmental Contamination and Toxicology, 2020)

Organic Matter Pollution During the Spring Thaw in Hulun Lake Basin: Contribution of Multiform Human Activities - Wenlin Wang; Wenjing Li; Yan Yan; Bo Liu; Tanjing Wang; Sichen Mao; Linhui Song; Huashan Dou; Wen Ao; Changxin Zou (Bulletin of Environmental Contamination and Toxicology, 2020)

Transcriptomic analysis reveals key early events of narciclasine signaling in Arabidopsis root apex - Xiaoning Cao; Fei Ma; Tingting Xu; Junjie Wang; Sichen Liu; Gaihong Li; Qian Su; Zhijun Qiao; XiaoFan Na (Plant Cell Reports, 2016)